Role of T Regulatory Cells and Myeloid-Derived Suppressor Cells in COVID-19 - Alhasan Alsalman; Mohammad A. Al-Mterin; Eyad Elkord (Journal of Immunology Research)
Coronavirus disease 2019 (COVID-19) has been raised as a pandemic disease since December 2019. Immunosuppressive cells including T regulatory cells (Tregs) and myeloid-derived suppressor cells (MDSCs) are key players in immunological tolerance and immunoregulation; however, they contribute to the pathogenesis of different diseases including infections. Tregs have been shown to impair the protective role of CD8+ T lymphocytes against viral infections. In COVID-19 patients, most studies reported reduction, while few other studies found elevation in Treg levels. Moreover, Tregs have a dual role, depending on the different stages of COVID-19 disease. At early stages of COVID-19, Tregs have a critical role in decreasing antiviral immune responses, and consequently reducing the viral clearance. On the other side, during late stages, Tregs reduce inflammation-induced organ damage. Therefore, inhibition of Tregs in early stages and their expansion in late stages have potentials to improve clinical outcomes. In viral infections, MDSC levels are highly increased, and they have the potential to suppress T cell proliferation and reduce viral clearance. Some subsets of MDSCs are expanded in the blood of COVID-19 patients; however, there is a controversy whether this expansion has pathogenic or protective effects in COVID-19 patients. In conclusion, further studies are required to investigate the role and function of immunosuppressive cells and their potentials as prognostic biomarkers and therapeutic targets in COVID-19 patients.